Transition Management of Knowledge Workforce in The Grasberg Surface Mine and Underground Mine (The Indonesian Journal of Business Administration, 2015)
Abstract – PT. Freeport Indonesia is a subsidiary company of Freeport McMoRan Copper & Gold Inc. (FCX) which hold 81.28% of its share, GOI (9.36%), and PT. Indocopper Investama (9.36%). PTFI was establish on April 8th, 1967, which the main business is produce and distributing concentrate copper and gold. Grasberg Surface Mine was contributing 80% of concentrate production for all PTFI revenue’s since 26 years ago and will be closure by early 2018. Safety slope stability issue is become the main reason to closure the Grasberg surface mine, then will be continued by using block cave technic of underground mine – Grasberg Block Caving ( GBC). Grasberg mineral district have a remaining deposit of minerals ore 2.4 million tons. In line with  the developing of infrastructure which estimating require of capital around US $ 16 billion since 4 years, GBC also posting the manpower requirement. In other side Grasberg will have a surplus manpower due to ramping down of production afterward the mine closure. Currently PTFI faced strategic problem related the manpower such as (i) termination of 1,271 Grasberg manpower is need huge cost for final payment, and will impacted to PTFI reputation as a mining operator in Indonesia and also negative impact to drop of share price (ii) the limitation of availability manpower experienced in underground miner to fulfil underground manpower requirement (iii) Grasberg workforce knowledge transition was built to assessment shifting the manpower from Grasberg to Underground mine (iv) Resistance of manpower mixing with gap competencies & skill to-be job in underground  need to be created strategy and approach (v) Timing gaps between Grasberg manpower released plan as supplied and underground mine manpower requirement schedule as demand have possibility disturbing the ore production goals.  Therefore in anticipation the manpower problem issue with some potential alternatives (i) Transition management program of knowledge workforce strategy and approach (ii) Enrichment and reskilling program of basic competencies (iii) Organizational change which lead by change management (iv) Involving all stakeholder to support change management.  Keywords: Knowledge Workforce, Transition Management, General Environment Analysis, Five Forces of Competitor, QSPM, The Jay Galbraith Star Model, Force Field Analysis, Change Management